Perceptions of Organizational Politics among Public Sector University Faculty (Journal of Education and Educational Development, 2022)
The fact that politics exist in Pakistani associations is true for the education sector too. This research distinguished whether maintaining, moving higher in a brief time frame, in the hierarchy of a higher education institution, is through belongingness or is it through labour and capability. This study investigated the existence of politics among the teachers of public sector higher education institutions and is structured around the Perceptions of Organizational Politics (PoPs) developed by Kacmar and Carlson (1997). The data was collected in two phases: the first phase included the collection of quantitative data from 367 university faculty and in the second phase 15 university Deans/ HoDs were interviewed for triangulation. The data collected was analyzed using SPSSv-22.0. The results of the research established that politics exists at the university level and that seats of learning are not exempted from the evil of politics; teachers act the same way as workers in any other organization. The research likewise brought to the fore a solid relationship between workers’ apparent contentment with regards to pay and advancement and organizations’ compensation and advancement guidelines.